2003
DOI: 10.1128/jvi.77.2.1578-1583.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus F Protein Is a Short-Lived Protein Associated with the Endoplasmic Reticulum

Abstract: Hepatitis C virus (HCV) F protein is a newly discovered HCV gene product that is expressed by translational ribosomal frameshift. Little is known about the biological properties of this protein. By performing pulse-chase labeling experiments, we demonstrate here that the F protein is a labile protein with a half-life of <10 min in Huh7 hepatoma cells and in vitro. The half-life of the F protein could be substantially increased by proteasome inhibitors, suggesting that the rapid degradation of the F protein is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 30 publications
4
64
0
5
Order By: Relevance
“…The predicted instability indices for the core11/F and core11/S proteins were 45.63 and 51.91, respectively (29). The core11/F protein synthesized in vitro or in cultured Huh7 cells has indeed been shown, in pulse-chase labeling experiments, to be a short-lived protein with a half-life of 10 min (28,31). Its degradation has been shown to be markedly inhibited by proteasome inhibitors (MG132, lactacystin).…”
Section: Biochemical Properties Of Core11 Proteinsmentioning
confidence: 98%
See 3 more Smart Citations
“…The predicted instability indices for the core11/F and core11/S proteins were 45.63 and 51.91, respectively (29). The core11/F protein synthesized in vitro or in cultured Huh7 cells has indeed been shown, in pulse-chase labeling experiments, to be a short-lived protein with a half-life of 10 min (28,31). Its degradation has been shown to be markedly inhibited by proteasome inhibitors (MG132, lactacystin).…”
Section: Biochemical Properties Of Core11 Proteinsmentioning
confidence: 98%
“…The core11/F protein of genotype 1a has been detected by various groups in the cytoplasm of human hepatoma (Huh7, HepG2) cells, in the perinuclear area, and associated with the endoplasmic reticulum (ER) membrane (28,31,74). Only one study has reported the presence of core11/F in the nucleus, in human embryonic kidney (HEK293) cells.…”
Section: Biochemical Properties Of Core11 Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…HCV structural proteins are processed and mature in close association with the ER (Lindenbach and Rice, 2005;Xu et al, 2003). When the ER is stressed by virus, calcium depletion or accumulation of misfolded proteins, it activates the unfolded protein response and triggers alterations in calcium homeostasis and secondary mitochondrial effects (Benali-Furet et al, 2005;Liberman et al, 1999;Pavio et al, 2003;Tardif et al, 2002;Tardif et al, 2005); (Gong et al, 2001).…”
Section: Discussionmentioning
confidence: 99%